LILIN AROMATIK MINYAK ATSIRI KULIT BATANG KAYU MANIS (Cinnamomum burmannii) SEBAGAI REPELEN LALAT RUMAH (Musca domestica) - Prasetyorini Djarot; Moerfiah .; Dwi Ambarwati (EKOLOGIA, 2019)
This research was aimed to create aromatic candle, infused with cinnamon (Cinnamomum burmanii) bark essential oil, which is a potential repellant for house fly (Musca domestica).  The distillation of akar wangi samples was carried out at the Spice and Aromatic Research Unit by vapor distillation method for 9-12 hours. The aromatic candles were based on a mixture of solid paraffin and stearin in a 2:8 proportion, respectively, enriched with fragrant root bark essential oils with 5 formulas, namely F1 (placebo), F2 (fixative), F3 (1% essential oil), F4 (2% essential oil), and F5 (3% essential oil).  The repellency test was carried out by inserting 20 house flies in a of 50x50x50 cm container that contains a lighted aromatic candle according to the doses mentioned above, and shrimp scalps located 15 cm from the candle that functions as a bait. The calculated parameters were the hourly number of flies that were allured to the bait for 6 hours, which were related to the candle’s repellency and the house fly’s preference of candle. The repulsion ability result were 89.724%, 75.28%, 68.06%, 49.17%, 9.72% for F5, F4, F3, F2, and F1, respectively. The result also showed that the F4 sample was the most preferred sample.